2006
DOI: 10.1074/jbc.m513447200
|View full text |Cite
|
Sign up to set email alerts
|

The Metabotropic Glutamate G-protein-coupled Receptors mGluR3 and mGluR1a Are Voltage-sensitive

Abstract: G-protein-coupled receptors play a key role in signal transduction processes. Despite G-protein-coupled receptors being transmembrane proteins, the notion that they exhibit voltage sensitivity is rather novel. Here we examine whether two metabotropic glutamate receptors, mGluR3 and mGluR1a, both

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
70
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 48 publications
6
70
0
Order By: Relevance
“…4). This finding is in agreement with previous studies that demonstrated voltage-dependent modulation of G-protein mediated signaling pathways, such as the regulation of G-protein regulated K + -channels or Ca 2+ -activated Cl − channels and the liberation of Ca 2+ from intracellular Ca 2+ stores (4,7,10,26). A unique aspect from this study is the finding that the recruitment of β-arrestin to active receptors, which induces G protein-independent receptor signaling pathways, also exhibits voltage-dependence.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…4). This finding is in agreement with previous studies that demonstrated voltage-dependent modulation of G-protein mediated signaling pathways, such as the regulation of G-protein regulated K + -channels or Ca 2+ -activated Cl − channels and the liberation of Ca 2+ from intracellular Ca 2+ stores (4,7,10,26). A unique aspect from this study is the finding that the recruitment of β-arrestin to active receptors, which induces G protein-independent receptor signaling pathways, also exhibits voltage-dependence.…”
Section: Discussionsupporting
confidence: 82%
“…This lower affinity for NE at positive voltages without a G protein docked to the receptor is not in line with the current model of voltage-sensitivity in GPCRs, which is based on the observation that voltage selectively affects the high-affinity state of the receptor, which requires coupling to G proteins. Indeed, such voltage-induced changes in receptor affinity were abolished by PTX treatment in case of the muscarinic M 2 receptor for acetylcholine (7,13). Because the voltagesensitivity of the α 2A AR-cam is clearly present in PTX-treated cells, we conclude that α-adrenergic receptors exhibit voltagesensitivity via an alternative mechanism that is independent from G-protein coupling.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…It was recently reported that mGluR activation was voltage sensitive (32,33). We tested this possibility with the hope that depolarization-induced shift of the dose-response would enable kinetic analysis with perfect time resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Although GPCRs span the cell membrane, they were not considered to be affected by voltage. Recently, it was shown that depolarization affects the activity of various GPCRs belonging to classes A and C (1)(2)(3)(4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%